Governing Refugees: Justice, Order and Legal Pluralism, by Kirsten McConnachie - Purkey, Anna (Refuge: Canada’s Journal on Refugees, 2014)
Governing Refugees: Justice, Order and Legal Pluralism by Kirsten McConnachie Abingdon, UK: Routledge, 2014, pp. 200